Analysis and Pollution Assessment of Brominated Flame Retardants (PBDEs, DBDPE, and BTPBE) in Settled Dust from E-waste and Vehicle Processing Areas in Northern Vietnam - Anh, Hoang Quoc; Minh, Trinh Hai; Minh, Pham Dang; Nhat, Tu Minh; Minh, Nguyen Le Hong; Minh, Tu Binh; Takahashi, Shin (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 3DO - 10.25073/2588-1140/vnunst.5525, 2023)
Polybrominated diphenyl ethers (PBDEs), decabromodiphenyl ethane (DBDPE), and 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE) are typical brominated flame retardants (BFRs), which were widely added to polymeric and textile materials to meet fire safety requirements. PBDEs (including commercial penta-, octa-, and deca-BDE mixtures) have been classified as persistent organic pollutants (POPs) under the Stockholm Convention, while DBDPE and BTBPE are considered as PBDE replacements. In the present study, concentrations of PBDEs (major congeners of technical PBDE mixtures such as BDE-28, 47, 99, 100, 153, 154, 183, 197, 207, and 209), DBDPE, and BTBPE were simultaneously analyzed in settled dust samples collected from e-waste and end-of-life vehicle (ELV) processing areas in northern Vietnam. The dust samples were extracted by using an ultrasonic processor subsequently by acetone and acetone/hexane (1:1) mixture for 10 min each time. The dust extract was treated with concentrated sulfuric acid and activated silica gel to remove interferences. BFRs were analyzed by using gas chromatography/mass spectrometry (GC/MS) equipped with a DB-5ht column. The mass spectrometer was operated at electron capture negative ionization (ECNI) and selected ion monitoring (SIM) mode. Concentrations of total PBDEs, DBDPE, and BTBPE ranged from 77 to 240,000 (median 6000), from <20 to 240,000 (median 5500), and from <10 to 9200 (median 160) ng/g, respectively. Concentrations of BFRs in the e-waste dust were significantly higher than those measured in the ELV dust, suggesting e-waste processing activities as potential sources of BFRs in dust. Among BFRs analyzed, BDE-209 and DBDPE were the most predominant compounds, implying intensive application of deca-BDE mixtures and alternative formulations.